Learning in India's primary schools: How do disparities widen across the grades?. (September 2017) - Alcott, Benjamin; Rose, Pauline
Highlights: Wealth is a strong determinant of learning disparities, even from the beginning of primary school in rural India. While large wealth gaps exist throughout rural India, the prevalence of gender disparities varies across states. The SDGs should include a target for learning in the early years, disaggregated by wealth, gender and other markers of disadvantage. The findings suggest that countries need to put in place strategies to alleviate the impact of poverty on learning, even before children start school. Abstract: Using a large-scale household survey, we investigate how disparities in learning change over the primary school cycle. Even controlling for other factors, household wealth and parental schooling drive sizeable gaps in learning, increasing in magnitude over the school grades. Gender gaps also widen, although only among the poorest. In contrast to other countries, overage status is positively associated with learning early on, but its importance dissipates by later grades. While the importance of factors varies across states, household wealth predominates. The analysis highlights the importance of tackling disadvantage associated with poverty early, to avoid its effects on learning becoming entrenched.